MEMPERKUAT BUDAYA PERUSAHAAN MELALUI EKSISTENSI DAN INDEPENDENSI PUBLIC RELATIONS: Studi di PT Indonesia Power UJP Banten II Labuan - Susilawati, Eka (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
This research aims to find out the existence of public relations structurally in the company in socializing corporate culture at PT Indonesia Power UJP Banten II Labuan. The research was conducted using qualitative methods through structured interviews at Public Relations at PT Indonesia Power UJP Banten II Labuan. The results showed that the existence of public relations structurally at PT Indonesia Power UJP Banten II Labuan has not been independent because it is still incorporated into a unit in the Administrative Division. Public Relations in socializing corporate culture at PT Indonesia Power UJP Banten II Labuan in collaboration with the Human Resources Division (HR) through three forms of socialization, namely face-to-face, online media and print media